The Substantive Impact of Computers on Philosophy Prolegomena to a Computational and Information-Theoretic Metaphysics. - Dipert, Randall R. (Metaphilosophy, 2002)
I survey in this article the practical uses of computers in philosophy: except for logic, computers have not yet noticeably improved the quality of philosophizing, research, or pedagogy. They have made work easier. My main interest, however, is in the “substantive” impact that computers may have on philosophical problems, especially in metaphysics. I argue that logic, the notion of decidability, and the theory of computation all predated and did not require modern digital computers. In the philosophy of mind, there has been a persistent conflation of computationalism and physicalism. The two theses can and should be separated. Finally, I suggest that we see glimpses of a new metaphysics based on information and information transformations that goes far beyond the well-trodden mind-brain debates.